2007
DOI: 10.1002/pola.22171
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of novel poly(p‐phenylenevinylene) derivatives containing phenothiazine‐5‐oxide and phenothiazine‐5, 5‐dioxide moieties

Abstract: PPV-based copolymers containing phenothiazine-5-oxide and phenothiazine-5, 5-dioxide moieties have been successfully synthesized by Wittig-Horner reaction and characterized by means of UV-vis, photoluminescence, electroluminescence spectra, and cyclic voltammetry. All of these copolymers can be dissolved in common organic solvents such as chloroform, tetrahydrofuran, and toluene. The PL maxima in the film state are located at 582, 556, and 552 nm for P1, P2, and P3, respectively. The HOMO and LUMO levels of P2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…Phenothiazine contains electron-rich atoms N and S atoms, possesses a low oxidation potential, and is capable to form stable cation-radicals. The unique electronic and optical characteristics of phenothiazine proceed from its nonplanar geometry providing thereby the possibility to obtain π-packed aggregates and intermolecular excimers [5]. It has been established in our previous research that chalcones prepared on the base of carbazole, phenothiazine, and their substituted derivatives appeared to be good for creation of electrochromic polymer films [6][7][8].…”
mentioning
confidence: 99%
“…Phenothiazine contains electron-rich atoms N and S atoms, possesses a low oxidation potential, and is capable to form stable cation-radicals. The unique electronic and optical characteristics of phenothiazine proceed from its nonplanar geometry providing thereby the possibility to obtain π-packed aggregates and intermolecular excimers [5]. It has been established in our previous research that chalcones prepared on the base of carbazole, phenothiazine, and their substituted derivatives appeared to be good for creation of electrochromic polymer films [6][7][8].…”
mentioning
confidence: 99%
“…Recently, phenothiazine polymers have been used in PLEDs,7–11 organic field‐ effect transistors (OFETs),12, 13 and organic solar cells,7, 12, 14–17 due to their good electro‐optical properties. Due to its electron‐rich nature, phenothiazine is an excellent building block for lowering the ionic potential of conjugated polymers and for promoting better injection and transportation of holes across the polymeric backbone 10, 18. Phenothiazine polymers also display higher quantum efficiencies as its nonplanarity prevents π‐stacking aggregation and intermolecular excimer formation 19, 20.…”
Section: Introductionmentioning
confidence: 99%
“…In spite of these properties, all the reported phenothiazine polymers have relatively poor light‐emitting performance. A few research groups have reported phenothiazine copolymers for PLED application 7–10. For example, Jenekhe and co‐workers20 have shown that an alternating copolymer of phenothiazine and fluorene displayed an improved PLED performance as compared with the phenothiazine homopolymer due to a more balanced electron and hole transport 20…”
Section: Introductionmentioning
confidence: 99%
“…As the phenothiazine unit has two electron‐rich sulfur and nitrogen heteroatoms, phenothiazine‐based polymers are good electron‐donors and hole transport materials, which have been investigated in LEDs9, 13–19 and PVDs 9, 19, 20. Recently, a phenothiazine‐based polymer, poly(3,7‐divinylene‐ N ‐octyl‐ phenothiazine‐alt‐2‐octyl‐benzotriazole) (PQTN), was synthesized in our laboratory according to the donor–acceptor‐alternating strategy 13.…”
Section: Introductionmentioning
confidence: 99%